(untitled) - Rangwala, Abdulla S. (New York, 2005)
Written by an author with more than three decades' experience in the field of machinery structural dynamics, Turbo-Machinery Dynamics details the latest methods for analyzing new design procedures, maximizing structural integrity, establishing component operating life, and controlling exhaust emissions. Within this text readers will find all the highly specialized data required to assist in the development and analysis of the cleanest and most cost-effective turbo-machinery possible.
Keywords: Turbines,Tua bin; Design and construction,Thiết kế và cấu tạo